Trajetórias no design de interação de terceira onda: participações, seus rastros, suas viradas - Kira, Gustavo (2016)
This work aims to show that Andrew's Feenberg Critical Theory can be used as basis to a reflection about the history and epistemology of CHI, especially the relations forged by the introduction of the term "Third Wave CHI". Besides, still using STS, we also aim to understand how concepts like participation, user, design and art can endorse practices in this field of knowledge. To accomplish this, we created a citation network about the "Third Wave CHI" gathering texts from the ACM (Association for Computing Machinery) database. At last, compare concepts that exists in the work of Helio Oiticica aiming to contribute with the discussion about participation, design and art.